Associations of circulating insulin-like growth factor-I with intake of dietary proteins and other macronutrients. Issue 7 (July 2021) - Watling, Cody Z.; Kelly, Rebecca K.; Tong, Tammy Y.N.; Piernas, Carmen; Watts, Eleanor L.; Tin Tin, Sandar; Knuppel, Anika; Schmidt, Julie A.; Travis, Ruth C.; Key, Timothy J.; Perez-Cornago, Aurora
Summary: Background & aims: Circulating insulin-like growth factor-I (IGF-I) is associated with the risk of several cancers. Dietary protein intake, particularly dairy protein, may increase circulating IGF-I; however, associations with different protein sources, other macronutrients, and fibre are inconclusive. To investigate the associations between intake of protein, macronutrients and their sources, fibre, and alcohol with serum IGF-I concentrations. Methods: A total of 11, 815 participants from UK Biobank who completed ≥4 24-h dietary assessments and had serum IGF-I concentrations measured at baseline were included. Multivariable linear regression was used to assess the cross–sectional associations of macronutrient and fibre intake with circulating IGF-I concentrations. Results: Circulating IGF-I concentrations were positively associated with intake of total protein (per 2.5% higher energy intake: 0.56 nmol/L (95% confidence interval: 0.47, 0.66)), milk protein: 1.20 nmol/L (0.90, 1.51), and yogurt protein: 1.33 nmol/L (0.79, 1.86), but not with cheese protein: −0.07 nmol/L (−0.40, 0.25). IGF-I concentrations were also positively associated with intake of fibre (per 5 g/day higher intake: 0.46 nmol/L (0.35, 0.57)) and starch from wholegrains (Q5 vs. Q1: 1.08 nmol/L (0.77, 1.39)), and inversely associated with alcohol consumption (>40 g/day vs <1 g/day: −1.36 nmol/L (−1.00, −1.71)). Conclusions: These results show differing associations with IGF-I concentrations depending on the source of dairy protein, with positive associations with milk and yogurt protein intake but no association with cheese protein. The positive association of fibre and starch from wholegrains with IGF-I warrants further investigation.